Manual‐guided cognitive–behavioural therapy for insomnia delivered by ordinary primary care personnel in general medical practice: a randomized controlled effectiveness trial. (16th July 2013) - Bothelius, Kristoffer; Kyhle, Kicki; Espie, Colin A.; Broman, Jan‐Erik
Summary Chronic insomnia is a prevalent problem in primary health care and tends to be more serious than insomnia in the general population. These patients often obtain little benefit from hypnotics, and are frequently open to exploring various options for medical treatment. However, most general practitioners (GPs) are unable to provide such options. Several meta‐analyses have shown that cognitive–behavioural therapy (CBT) for insomnia results in solid improvements on sleep parameters, and a few studies have demonstrated promising results for nurse‐administered CBT in primary care. The aim of this randomized controlled study was to investigate the clinical effectiveness of manual‐guided CBT for insomnia delivered by ordinary primary care personnel in general medical practice with unselected patients. Sixty‐six primary care patients with insomnia were randomized to CBT or a waiting‐list control group. The CBT group improved significantly more than the control group using the Insomnia Severity Index as the outcome. The effect size was high. Sleep diaries showed a significant, medium‐sized treatment effect for sleep onset latency and wake time after sleep onset. However, for all measures there is a marked deterioration at follow‐up assessments. Almost half of the treated subjects (47%) reported a clinically relevant treatment effect directly after treatment. It is concluded that this way of delivering treatment may be cost‐effective.